1979
DOI: 10.1159/000176256
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Animal Proteins on the Absorption of Food Iron in Man

Abstract: The way in which meat and fish act to promote the absorption of nonheme iron in food is not known. The present paper is a report of the results of a series of studies aimed at obtaining some insight into the mechanism of action of meat and other animal proteins on the absorption of food iron. Beef, fish, chicken and calf thymus all increased the iron absorption to about the same extent. Neither egg albumin, cysteine or a water extract of beef did, however, affect the absorption of food iron. Beef increased the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(54 citation statements)
references
References 17 publications
3
51
0
Order By: Relevance
“…It appears to exert its influence on the intraluminal milieu and does not seem to act indirectly by stimulating gastric secretion of hydrochloric acid. In one study, meat increased absorption from maize from 0.7% to 2.1% in patients with histamine-fast achlorhydria (Bjorn-Rasmussen & Hallberg, 1979). The three-fold greater absorption with meat is similar to that observed in other studies with normal individuals (Table I).…”
Section: Mechanism By Which Proteins Affect Iron Bioavailabilitysupporting
confidence: 74%
See 1 more Smart Citation
“…It appears to exert its influence on the intraluminal milieu and does not seem to act indirectly by stimulating gastric secretion of hydrochloric acid. In one study, meat increased absorption from maize from 0.7% to 2.1% in patients with histamine-fast achlorhydria (Bjorn-Rasmussen & Hallberg, 1979). The three-fold greater absorption with meat is similar to that observed in other studies with normal individuals (Table I).…”
Section: Mechanism By Which Proteins Affect Iron Bioavailabilitysupporting
confidence: 74%
“…The three-fold greater absorption with meat is similar to that observed in other studies with normal individuals (Table I). Further evidence for an intraluminal effect was provided by the observation that meat did not increase absorption from a solution of ferrous sulfate, but nevertheless, reduced the inhibitory effect of sodium phytate on absorption from both ferrous sulfate and ferric chloride (Bjorn-Rasmussen & Hallberg, 1979). The possibility that the effect of meat might be due to it's nucleoprotein content was considered by Bjorn-Rasmussen and Hallberg, but calf thymus which is particularly rich in nucleoproteins had a promoting effect that was no greater than that of other meat products.…”
Section: Mechanism By Which Proteins Affect Iron Bioavailabilitymentioning
confidence: 99%
“…Bjorn-Rasmussen and Hallberg (44) reported that the addition of chicken, beef, or fish to a maize meal increased nonheme iron absorption 2-3-fold with no influence of the same quantity of protein added as egg albumin. More recently, Baech et al (45) reported a dose-response increase in iron absorption when pork meat was added to a highphytate, low-ascorbic acid meal.…”
Section: Muscle Tissuementioning
confidence: 99%
“…There are contrasting views on the effect of ascorbic acid on the bioavailability of di etary iron, some showing good availability [31,32] and others poorer availability [33][34][35], Our own results favored high levels of plasma iron and greater synthesis of blood hemoglobin, especially with respect to the high-protein diet. The results agree with the work of McCall et al [27], which indicated that plasma iron concentration ranged above 100 pg/100 ml of plasma in rats that were fed a diet containing 240 mg/kg body weight.…”
Section: Discussionmentioning
confidence: 72%
“…While many reports [35][36][37][38] have emphasized the unique role of high-quality protein in the absorption of iron and the subsequent syn thesis of hemoglobin, the sources of protein seem to be the ultimate determinant of this efficiency. Rios et al [39] were unable to show a difference in iron absorption when they compared a milk-and soy-based formu la, which were both fortified with ascorbic acid.…”
Section: Discussionmentioning
confidence: 99%